New insights on slippery lubricant-infused porous surfaces technique in mitigating microbial corrosion - Ini-Ibehe Nabuk Etim; Ruiyong Zhang; Can Wang; Sikandar Khan; Krishnamurthy Mathivanan; Jizhou Duan (npj Materials Degradation)
Abstract Microorganisms in notable environments often impact metal corrosion—this characteristic is designated microbiologically-influenced corrosion (MIC), and its effect has led to the cost of material repairs. Some key measures adopted to mitigate MIC are protective coatings, slippery lubricant-infused porous surfaces (SLIPS), and corrosion inhibitors. Interestingly, SLIPS has been used recently as a novel technique in antifouling and biocorrosion applications. This is due to its liquid-repellent characteristic sliding angles of about <5° compared to other surfaces with a contact angle of about > 150°. In one of the studies, the slippery lubricant surfaces displayed the superlative anti-biofouling characteristics by reducing the fouled region by <10% for about 72 h irrespective of the underlying layer of the substrate. This review provides an updated overview of the developments in SLIPS technology, focusing on its application in mitigating MIC across environments.